Mineral Exploration: Practical Application - Roonwal, G.S (Springer Geology,, 2018)
The book introduces essential concept of mineral exploration, mine evaluation and resource assessment of the discovered mineral deposit to students, beginners and professionals. The book is divided into nine chapters which will help the readers to incorporate the concepts of search for mineral deposits and understand the chances of success. The book discusses the fundamental details like composition of earth and mineral resources, formation of rock and mineral deposits, and the attempt to search for ore deposits to advance applications of remote sensing in mineral exploration. It also covers the details on how to conduct system of survey, evaluation, and how to arrive at a decision to open and carryout further exploration in the operating mine. The book shall be of great interest to geologists and mining community.